Evaluación del efecto de la temperatura de calcinación de la ilmenita sobre la actividad microbiana en presencia de luz visible (2017)
The machines were evaluated to be effective in the removal of methylene blue for the applications of microbiological degradation, after establishing the conditions in the theoretical foundations, a removal of 73.3% of methylene blue in 215 minutes at From ilmenite thermally modified to 650 ° C. The McFarland standard was then used, where an initial concentration of 10 8 was estimated, which was exposed in a photoreactor in visible light together with a film of Ilmenite supported in polystyrene for 9 Hours where it was observed by a plate count that the ilmenite supported in polystyrene is not effective in microbiological degradation over time.